2015
DOI: 10.1111/jfpe.12185
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metal Contamination from Peanut Skin Extracts by Waste Biomass Adsorption

Abstract: Peanut skins are a processing waste product with potential as a low‐cost source of polyphenols for nutraceutical or functional food ingredient use. Aqueous extractions of peanut skins and subsequent concentration of these extracts can result in normally innocuous levels of heavy metals present to be increased to concentrations of human health concern. Adsorption utilizing waste biomasses is a promising method of removing these contaminants from extracts. Peanut hulls and chitosan cross‐linked beads were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Peanut hulls 21.7±9.5% of arsenic and 88.6±1.9% of cadmium removal [66] Peanut husk Ultrasound assisted chemically activated peanut husk shows 19.6 mg/g of copper adsorption [67] under various pyrolysis temperatures (300ºC to 800ºC). The DMB3 (prepared at 300ºC) has shown higher yield and surface oxygen-containing group content as compared to that prepared at higher pyrolysis temperatures (500ºC and 800ºC).…”
Section: Waste Tea Leavesmentioning
confidence: 99%
“…Peanut hulls 21.7±9.5% of arsenic and 88.6±1.9% of cadmium removal [66] Peanut husk Ultrasound assisted chemically activated peanut husk shows 19.6 mg/g of copper adsorption [67] under various pyrolysis temperatures (300ºC to 800ºC). The DMB3 (prepared at 300ºC) has shown higher yield and surface oxygen-containing group content as compared to that prepared at higher pyrolysis temperatures (500ºC and 800ºC).…”
Section: Waste Tea Leavesmentioning
confidence: 99%
“…Peanut was bought from a local market in Bangkok, Thailand. The preparation of peanut shell agrowaste methodology was modified from Arunlertaree and coauthors [26] and Massie and coauthors [27]. First, the peanut was washed thoroughly with tap water to minimize its chromaticity and remove any dirty.…”
Section: Adsorbent Preparationmentioning
confidence: 99%
“…Ogata et al reported that a waste biomass adsorbent produced from mangosteen shells (MGS1000) exhibited a good adsorption capacity of 12.0 mg/g for adsorbing cadmium ions from aqueous media . In addition, rice husk, saw dust, corn stalk, peanut skins, and coconut waste were found to be effective in removal of heavy ions. However, the single biomass adsorbent was commonly limited in practical applications due to its undesirable adsorption capacity, thus the modification treatment was selected to the enhancement of active sites, like surface functional groups and specific surface area. …”
Section: Introductionmentioning
confidence: 99%